2009
DOI: 10.1007/s10856-009-3939-2
|View full text |Cite
|
Sign up to set email alerts
|

Densification, phase stability and in vitro biocompatibility property of hydroxyapatite-10 wt% silver composites

Abstract: In this paper, we demonstrate how a simple fabrication route, i.e., pressureless sintering of mechanically mixed powders can be employed to develop hydroxyapatite (HAp, Ca(10)(PO(4))(6)(OH)(2))-silver (Ag) bioceramic composites with superior combination of physical (hardness, toughness), non-cytotoxicity, cytocompatiblity and anti-microbial property. The densification results show that such composites can be sintered at 1200 degrees C for 2 h near to theoretical density (>98% rho(th).) An important observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 39 publications
2
64
0
4
Order By: Relevance
“…3 shows SEM micrograph of the YSZ-Ag sintered at 1400°C for 1 h. Near-equi-axial grains can be seen in close contact with a few voids, suggesting that the sintering process produces a dense compact. Although 10 wt% Ag has been reported to melt and locate to the grain boundaries in sintered hydroxyapatite [23], this cannot be observed in this study since only 0.5 wt% Ag was used. The surface topography of the YSZ-Ag, obtained by AFM, is shown in Fig.…”
Section: Microstructurementioning
confidence: 67%
See 1 more Smart Citation
“…3 shows SEM micrograph of the YSZ-Ag sintered at 1400°C for 1 h. Near-equi-axial grains can be seen in close contact with a few voids, suggesting that the sintering process produces a dense compact. Although 10 wt% Ag has been reported to melt and locate to the grain boundaries in sintered hydroxyapatite [23], this cannot be observed in this study since only 0.5 wt% Ag was used. The surface topography of the YSZ-Ag, obtained by AFM, is shown in Fig.…”
Section: Microstructurementioning
confidence: 67%
“…Comparing the antibacterial ability and mechanism of Ag containing alloys or composites [10,23,32,38,39] most of literatures conclude that Ag + -ions-release causes the bacteria-inhibiting effect. In this study, YSZ-Ag composites exhibited significant inhibiting effect when 0.5 wt% Ag was added.…”
Section: The Effect Of Ag-ions-release On Bacteria Inhibitingmentioning
confidence: 99%
“…Other studies also demonstrated the formation of this phase for various Ag + concentrations 8,9 . These studies demonstrated that inserting ions of different sizes and charges into HA could compensate for the structural stress caused by inserting a single type of ion.…”
Section: Introductionmentioning
confidence: 70%
“…(1-y/6)Ca 10 (PO 4 ) 6 (OH) 2 + (x+y)CO 2 + yCaO + yAg (6) After CO 3 2-is released from the HA structure, the excess Ca 2+ tends to form CaO, the inserted silver tends to form metallic silver 8,25 , and the remainder generates a stoichiometric hydroxyapatite. Thus, after calcination, the vibrational modes from OH -groups may be remarkably enhanced because of the better lattice organization and release of CO 3 2-from the structure.…”
Section: Vacancy Formationmentioning
confidence: 99%
“…Human osteoblast SaOS2 cell line, procured from ATCC, USA, was used to study the in vitro cytocompatibility of the as-synthesized bioceramics following the standard cell culture protocol, as described in our earlier work [16][17][18]. A plastic disc was used as control and the cell seeded samples were incubated in a CO 2 incubator for 72 h at 37°C.…”
Section: In Vitro Biocompatibility Propertiesmentioning
confidence: 99%